Rising from the ashes : Los Angeles, 1992 : Edward Jae Song Lee, Latasha Harlins, Rodney King, and a city on fire - Yoo, Paula (Norton Young Readers, an imprint of W.W. Norton & Company, 2024)
Paula Yoo's latest is a compelling, nuanced account of Los Angeles's 1992 uprising and its impact on its Korean and Black American communities. In the spring of 1992, after a jury returned not guilty verdicts in the trial of four police officers charged in the brutal beating of a Black man, Rodney King, Los Angeles was torn apart. Thousands of fires were set, causing more than a billion dollars in damage. In neighborhoods abandoned by the police, protestors and storeowners exchanged gunfire. More than 12,000 people were arrested and 2,400 injured. Sixty-three died. In Rising from the Ashes, award-winning author Paula Yoo draws on the experience of the city's Korean American community to narrate and illuminate this uprising, from the racism that created economically disadvantaged neighborhoods torn by drugs and gang-related violence, to the tensions between the city's minority communities. At its heart are the stories of three lives and three families: those of Rodney King; of Latasha Harlins, a Black teenager shot and killed by a Korean American storeowner; and Edward Jae Song Lee, a Korean American man killed in the unrest. Woven throughout, and set against a minute-by-minute account of the uprising, are the voices of dozens others: police officers, firefighters, journalists, business owners, and activists whose recollections give texture and perspective to the events of those five days in 1992 and their impact over the years that followed.